Effect of stress and peripheral immune activation on astrocyte activation in transgenic bioluminescent Gfap‐luc mice. Issue 7 (17th February 2015) - Biesmans, Steven; Acton, Paul D.; Cotto, Carlos; Langlois, Xavier; Ver Donck, Luc; Bouwknecht, Jan A.; Aelvoet, Sarah‐Ann; Hellings, Niels; Meert, Theo F.; Nuydens, Rony
Abstract : Neuroinflammation and the accompanying activation of glial cells is an important feature of many neurodegenerative conditions. It is known that factors such as peripheral infections and stress can influence immune processes in the brain. However, the effect of these stressors on astrocyte activation in vivo remains elusive. In this study, transgenic Gfap‐luc mice expressing the luciferase gene under the transcriptional control of the glial fibrillary acidic protein promoter were used to quantify the kinetics of in vivo astrocyte activation following immune challenges relevant to clinical inflammation. It was found that astrocytes respond rapidly to peripheral immune activation elicited by either bacterial lipopolysaccharide (LPS) or the viral mimetic polyinosinic:polycytidylic acid (poly(I:C)). By measuring bioluminescence and 18‐kDa translocator protein radioligand binding in the same animal it was observed that LPS induces both astrocyte as well as microglial activation at 6 h post‐administration. Furthermore, the astrocyte response decreased upon repeated systemic LPS injections, indicating development of tolerance to the LPS challenge. Finally, restraining Gfap‐luc mice for 1 h daily on 5 consecutive days did not affect brain bioluminescence, thereby indicating that sub‐chronic stress does not influence astrocyte activation under unchallenged conditions. However, stressed animals showed a reduced response to a subsequent systemic LPS injection, suggesting that the immune system is compromised in these animals. Here, we demonstrate that Gfap‐luc mice can be used to study astrocyte activation in response to stimuli relevant for clinical inflammation and that this approach may provide a more complete characterization of existing and novel models of neuroinflammation. GLIA 2015;63:1126–1137 Main Points: Systemic administration of LPS or poly(I:C) activates astrocytes in transgenic bioluminescent Gfap‐luc mice. Astrocyte activation decreases upon repeated LPS injections. Restraint stress reduces the astrocyte response to a subsequent LPS injection.